1990
DOI: 10.1111/j.1528-1157.1990.tb05512.x
|View full text |Cite
|
Sign up to set email alerts
|

Epidemiology of Epilepsy in Guaymi Indians from Bocas del Toro Province, Republic of Panama

Abstract: This cross-sectional study was conducted to describe the epidemiology of epilepsy in Guaymi Indians residing in Changuinola, a small town on Panama's Caribbean coast near Costa Rica. We randomly selected households and attempted to enroll all residents aged less than or equal to 1 year; 337 eligible subjects agreed to participate (93% response rate). We administered a standard neurologic disease screening examination to all subjects and, if any abnormality was found, we administered a standard neurologic evalu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

4
45
2
9

Year Published

1992
1992
2014
2014

Publication Types

Select...
4
3
1

Relationship

0
8

Authors

Journals

citations
Cited by 69 publications
(61 citation statements)
references
References 16 publications
4
45
2
9
Order By: Relevance
“…In recent years, many prevalence studies have been reported from developing countries with the same methods suggested by WHO. Some of the prevalence rates reported from rural areas of developing countries are as follows: 5.8/1,000 in Guatemala (lo), 10.2/1,000 in Tanzania ( 1 l), 2.47/1,000 in Kashmir, India (12), 57/1,0OO in the Guaymi Indian population of Panama (13), and 37/1,000 in Nigeria (14). In general, population-based WHO protocol studies have given an average prevalence rate of 18.5/1,000 (6).…”
Section: Discussionmentioning
confidence: 99%
“…In recent years, many prevalence studies have been reported from developing countries with the same methods suggested by WHO. Some of the prevalence rates reported from rural areas of developing countries are as follows: 5.8/1,000 in Guatemala (lo), 10.2/1,000 in Tanzania ( 1 l), 2.47/1,000 in Kashmir, India (12), 57/1,0OO in the Guaymi Indian population of Panama (13), and 37/1,000 in Nigeria (14). In general, population-based WHO protocol studies have given an average prevalence rate of 18.5/1,000 (6).…”
Section: Discussionmentioning
confidence: 99%
“…Estudos, embora com metodologias diferentes, mas também com bases populacionais urbanas no Brasil, mostram resultados similares 3,4 . Gracia et al 6 , usando metodologia semelhante, estudaram a prevalência de epilepsia na população dos índios Guaymis no Panamá. Encontraram a surpreendente prevalência de 57‰, sendo este fato relacionado ao fator de risco "antecedentes familiares"; em estudo na população urbana da cidade do Panamá, encontraram prevalência de epilepsia ativa de 22‰ 20 .…”
Section: Discussionunclassified
“…A investigação epidemiológica para determinar a freqüência, a distribuição e os fatores de risco desta entidade se faz necessária e deve ser representativa entre as diversas populações de um país 4 . Os resultados dos estudos epidemioló-gicos sobre epilepsia têm apontado ampla faixa de variação como valores entre 0,9‰ habitantes 5 e 57‰ 6 para a prevalência e 26/100000/ano 7,8 para a incidência. As referidas variações podem representar diferenças entre as populações estudadas em consequência de fatores tais como o serviço inadequado de saúde pública (particularmente os cuidados perinatais), o programa de vacinação, a exposição a agentes infecciosos ou infestantes como cisticercose e o trauma crânio-encefálico, embora questões metodológicas possam contribuir ou ser a razão de resultados tão distintos 4 .…”
unclassified
See 1 more Smart Citation
“…A taxa de prevalência de epilepsia nos países desenvolvidos varia de 3 -8/1000 4,5 , ao passo que na América Latina, nos países em desenvolvimento, essa taxa se encontra em torno de 3 -57/1000 6,7 . Se nos países desenvolvidos se observa maior taxa de prevalência nas idades extremas da vida, nos países latino-americanos são relatadas as maiores taxas de prevalência, entre 15 -40 anos de idade 8,9 .…”
Section: Epilepsias Criptogênicas Caracterizam-se Por Crises Epilépticasunclassified